Қазақ-қарақалпақ фольклоры менен әдебияты байланысларының айырым өзгешеликлери (FAN va JAMIYAT, 2017)
The article deals with the study Kazakh and Karakalpak influence, excessive improvement of national lit- erature ideological thematic and genre, development from the point of view of form and achievement of na-